Role Of Management To Communicate The Excellent Hospitality For Hotel Business - Kencana Herdianto Eling Asmara; Yenni, Yenni; Harliantara, Harliantara; Rosalia Erta Prawesti; Zulaikha, Zulaikha (SEAN Institute, 2024)
This study delves into the important role of management in effectively communicating exceptional hospitality within the hotel industry. The introduction emphasizes the significance of effective communication in achieving high levels of client satisfaction and loyalty in the highly competitive hospitality industry. The study of literature provides a thorough assessment of recent research on staff involvement, customer experience, and management communication strategies. It emphasizes the need for further research and suggests potential opportunities for more comprehensive studies. The methodology section provides a comprehensive approach to data collection, incorporating qualitative interviews with hotel management, employees, and guests. The results indicate that effective, coherent, and compassionate communication of leadership has a positive impact on the quality of service, employee motivation, and customer happiness. Based on the study, the development of a strong corporate culture and the provision of exceptional hospitality rely on the implementation of effective communication strategies. It offers hotel managers practical guidance on establishing effective channels of communication.